Globalization and World Order: Some Notes (Glocalism: Journal of Culture, Politics and Innovation, 2020)
Globalization conceived as the maximum compression of time and space “pulls away” from the nation-state while, at the same time, also “pushes down”. In other words, under the process of globalization, the system of local and parochial identity and loyalty is gradually supplemented with the system of multi-identity and multi-loyalty. The axial question concerns the compatibility/non-compatibility of the current unprecedented global system with a world made up of a plurality of civilizations – where civilization is defined as a junction between a world vision and a historical formation. In other words, can the world become economically global without having any substantial impact on civilizations?
Keywords: globalization; civilizations; world vision; historical formation; world order